FENOMENA CREDIT CRUNCH DI INDONESIA SELAMA MASA PANDEMIK COVID-19 PERIODE MARET 2020 – MARET 2021 SERTA FAKTOR PENYEBABNYA - Sahang Sapta Apritchzeki; Maria Evy Purwitasari (POLITEKNIK LP3I JAKARTA, 2021)
The Covid-19 pandemic that has occurred in the world has also greatly impacted Indonesia in various economic sectors, especially in the financial sector, especially the banking sub-sector. One of the phenomena that occurs is the decline in credit extended by banks to the public which makes it difficult for funds for people in need in the midst of the Covid-19 Pandemic. This phenomenon is known as the Credit Crunch. In this study, we will discuss the Credit Crunch Phenomenon that occurred in Indonesia during the Covid-19 pandemic. It was found that Indonesia experienced a Credit Crunch during the first period of the pandemic for the period March 2020 – March 2021. It was also found that the Credit Crunch that occurred was not due to a scarcity of funding sources.Key words: Credit Crunch, Funding, Fund